Bioretention Modelling Using Music Software For Urban Runoff Treatment Under Tropical Climate A Case Study In Universiti Sains Malaysia - Wong, Qi Min (Universiti Sains Malaysia, 2021)
Stormwater runoff pollution and flood problem are the major concerns in urban area due to the increase of imperviousness surface and human activities. Stormwater Best Management Practices (BMPs) such as wetland and bioretention have been introduced to solve these problems and the modelling software has been developed to predict the treatment performance of those stormwater BMPs facilities. In this project, MUSIC software is used to model the bioretention to treat polluted runoff in urban area under tropical climate. Due to frequent and dense rainfall patterns in tropics throughout the year, the rainfall-runoff process will be affected in the modelling. Hence, development of local meteorological template is essential for the modelling in this study. The bioretention model is simulated based on a pilot study in USM, Engineering Campus to evaluate the flow rate and pollutants reduction performance such as total suspended solids (TSS), total nitrogen (TN) and total phosphorus (TP). Two stages of calibration were conducted, with first stage is to calibrate the inflow and runoff pollutant concentrations based on the results measured on site, and second stage to further calibrate rate constant, k and background concentration, C* combination for each pollutants which fit to experimental results. The validation of model was done using the percentage bias between modelled and experimental data to evaluate the accuracy of bioretention modelling using MUSIC software. Overall, the performance of this model is fairly accurate as the performance rating is categorized as ‘very good’ or ‘satisfactory’.